The Quality of Peer Relationships as a Determinant of Learning Motivation Among Sixth-Semester Islamic Education Students - Fatma Izzatun Najwa; Helma Hidayati; Hilya Izatillah; Surawan Surawan (Edukasi, 2026)
Background – This study is motivated by the importance of teachers’ roles in managing effective learning, particularly at the elementary school level, where various instructional challenges often occur. In Indonesian language learning, listening skills are essential for supporting students’ language development, especially in lower grades. Research Urgency – Listening is a fundamental skill in language acquisition and classroom communication. At the early elementary level, weak listening skills may hinder students’ ability to understand instructions, process oral information, and participate actively in learning. Therefore, this study is important to identify the problems faced by teachers in teaching listening skills and to formulate practical strategies that can support more effective Indonesian language learning in lower grades. Research Objectives – This study aims to describe the problems encountered in teaching listening skills in Indonesian language learning and to identify teacher strategies for strengthening students’ listening skills at SD Negeri 1 Pondok. Research Method – This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. Interviews were conducted with teachers of grades 1, 2, and 3. Observations were carried out directly during classroom learning activities, while documentation was conducted by collecting relevant documents related to the learning process. The data were analyzed using the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing. Research Findings – The findings show that the problems of listening skills in Indonesian language learning in lower grades at SD Negeri 1 Pondok include students’ low concentration, limited learning motivation, and an unsupportive learning environment. These factors make it difficult for students to understand, process, and respond to oral information effectively. To overcome these problems, teachers apply several reinforcement strategies, such as using attractive learning media, including pictures and videos; implementing enjoyable learning methods, such as question-and-answer activities and role-playing; and conducting light, simple, and enjoyable evaluations. Conclusion – The study concludes that listening skill problems in lower-grade Indonesian language learning are mainly influenced by students’ concentration, motivation, and learning environment. Teacher strategies that integrate attractive media, interactive methods, and enjoyable evaluation activities can support the improvement of students’ listening skills. Research Novelty/Contribution – The novelty of this study lies in its emphasis on teacher-based practical strategies derived from real classroom needs. This study contributes concrete insights for elementary school teachers and education policymakers in designing more effective strategies to improve listening skills and the quality of Indonesian language learning in lower grades.